The art of timpani performance: stages of development - Vaslavskyi, Kyryl (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. Despite its long history of development, the art of solo performance on percussion instruments began to actively evolve only in the last century, achieving popularity among composers, performers, and listeners (unlike string, woodwind, and brass instruments) only in the second half of the 20th century. The timpani play a special role within the percussion family, combining rhythmic and pitch organization of sound. In this context, tasks related to the indepth analysis and systematization of the timpani repertoire become relevant for domestic musicology–particularly works written specifically for timpani, considering their intonational-thematic potential and technical performance specificity. The main objective of the study is to trace the historical evolution of the timpani as a solo instrument and to determine the stages and achievements along this path. The methodology includes the following methods: the principle of historicism serves as the methodological foundation; analytical method is used for working with scholarly literature; the method of historical-stylistic analysis and the analytical-descriptive method are used to define the specifics of timpani use in solo and orchestral performance; the method of performance analysis is applied to reveal the peculiarities of timpani playing in the works of composers from different eras; and theoretical generalization is used to draw conclusions. The main results and conclusions. The historical evolution of solo timpani playing passed through the following stages: the functional-signal phase (military-ceremonial, mid-XV – XVII centuries); the period of integration into orchestral practice and the appearance of isolated solo works (XVII—XIX centuries); the formation of an autonomous solo repertoire (mid-XX – XXI centuries). Over time, due to the instrument’s technical evolution, the creative potential of the timpani unfolded in various ways. Today, the timpani are not only one of the main instruments of the symphony orchestra but also a full-fledged solo instrument, capable of carrying a complete melody and serving as a central expressive color in the complex palette of contemporary musical composition. Solo performance on the timpani, beginning in the second half of the 20th century, is “in its prime”, finally asserting itself as a full-fledged type of solo performance art and gaining popularity among performer-timpanists, composers, and listeners. The continuous technical development of the instrument contributes to the emergence of virtuoso timpanists, whose skill inspires composers to new creative achievements, and they, in turn, continue to surprise audiences with new challenges for the virtuoso timpanists. It is not possible to cover the defined issues in full within the scope of a single article. Therefore, in the future, the horizons of research on the topic can be expanded through a more detailed study of the technical development of the timpani, the analysis of a greater number of compositions, and a deeper exploration of the specifics of national performance schools. Musical art is constantly in a state of active development, and according to the results of the study conducted, a significant number of new musical compositions can be expected, in which the timpani will play a bright and weighty role.